METHOD FOR PREDICTING OVARIAN HYPERSTIMULATION SYNDROME - Алина Владимировна Матросова; Сергей Петрович Пахомов; Антон Юрьевич Матросов; Умеда Гайбуллоевна Шокирова; Александра Сергеевна Устюжина (The Publishing House Medicine and Enlightenment, 2021)
The ovarian hyperstimulation syndrome (OHSS) is an iatrogenic syndrome, which may, infrequently, become severe and evenly fatal. Although the milder form is more common, particularly among patients undergoing gonadotropin stimulation for assisted reproductive technology, the severe form is rare. Unfortunately, there is currently no available way to predict this syndrome. This article aims develop a method for individual prediction of ovarian hyperstimulation syndrome. The aim of the study is to develop a method for individual prediction of ovarian hyperstimulation syndrome, based on socio-biological data, clinical and laboratory examination data and data obtained during ultrasound examination of the pelvic organs before entering the IVF protocol and during ovulation stimulation. Materials and methods. An analysis of 671 treatment cycles under the IVF program was carried out, among which 56 cycles were complicated by hyperstimulated ovarian syndrome. Results and its discussion. The aim of this study was to evaluate risk factors for development ovarian hyperstimulati on syndrome, which we considered in the aggregate with each other. Based on this, a method for individual prediction of the syndrome has been developed. Conclusions. We have developed a method for individual prediction of ovarian hyperstimulation syndrome with a sensitivity 93.9 %.